Moral Dilemmas and the Accountability of Criminal Offenders: A Neuroethical Perspective on Decision-Making in the Indonesian Criminal Justice System - Jubaidi, Didi; Khoirunnisa, Khoirunnisa; Indriastuti, Desy; Maharani, Shinta; L. Simanungkalit, Robert (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
Advancements in cognitive neuroscience are increasingly challenging traditional legal concepts of free will, intent, and individual culpability. In Indonesia, criminal liability remains grounded in classical legal doctrines that emphasize moral agency, raising critical questions about their compatibility with contemporary neuroethical insights. This article examines trauma, impulse control disorders, and cognitive dysfunction in criminal behavior from a neuroethical perspective, which can provide a more contextual understanding of criminal behavior in the Indonesian legal system. Using a qualitative normative method, this study combines doctrinal legal analysis with interdisciplinary approaches from neuroethics and moral psychology and compares jurisdictions that have recognized neuroscientific evidence in the criminal justice process. Using a qualitative normative method, this research integrates doctrinal legal analysis with interdisciplinary approaches from neuroethics and moral psychology, drawing comparative insights from jurisdictions that admit neuroscientific evidence in criminal adjudication. The study finds that although Indonesian law acknowledges mental incapacity in certain sentencing provisions, it lacks a consistent framework to assess neurocognitive impairments in determining guilt and punishment. As a result, current legal mechanisms may fail to adequately reflect the complex biological and moral dimensions of deviant conduct. This study concludes that integrating neuroethical considerations into Indonesian criminal law could improve its fairness, scientific relevance, and humaneness.